Co-Addition of Mg2Si and Graphene for Synergistically Improving the Hydrogen Storage Properties of Mg−Li Alloy - Huang, Xiantun; Liu, Haizhen; Duan, Xingqing; Lan, Zhiqiang; Guo, Jin (Frontiers in Chemistry, 2021)
Mg−Li alloy possesses a high hydrogen capacity. However, the hydrogenation and dehydrogenation performances are still far from practical application. In this work, Mg2Si (MS) and graphene (G) were employed together to synergistically improve the hydrogen storage properties of Mg−Li alloy. The structures of the samples were studied by XRD and SEM methods. The hydrogen storage performances of the samples were studied by nonisothermal and isothermal hydrogenation and dehydrogenation, thermal analysis, respectively. It is shown that the onset dehydrogenation temperature of Mg−Li alloy was synergistically reduced from 360 °C to 310 °C after co-addition of Mg2Si and graphene. At a constant temperature of 325 °C, the Mg−Li−MS−G composite can release 2.7 wt.% of hydrogen within 2 h, while only 0.2 wt.% of hydrogen is released for the undoped Mg−Li alloy. The hydrogenation activation energy of the Mg−Li−MS−G composite was calculated to be 86.5 kJ mol−1. Microstructure and hydrogen storage properties studies show that graphene can act as a grinding aid during the ball milling process, which leads to a smaller particle size for the composites. This work demonstrates that coaddition of Mg2Si and graphene can synergistically improve the hydrogen storage properties of Mg−Si alloy and offers an insight into the role of graphene in the Mg−Li−MS−G composite.